2016
DOI: 10.1021/acs.bioconjchem.6b00090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemically Modified Messenger RNA on Protein Expression

Abstract: Chemically modified nucleotides play significant roles in the effectiveness of mRNA translation. Here, we describe the synthesis of two sets of chemically modified mRNAs [encoding firefly Luciferase (FLuc) and enhanced green fluorescent protein (eGFP), respectively], evaluation of protein expression, and correlation analysis of expression level under various conditions. The results indicate that chemical modifications of mRNAs are able to significantly improve protein expression, which is dependent on cell typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(111 citation statements)
references
References 21 publications
1
101
0
Order By: Relevance
“…Alternatively, mRNAs with a complete substitution of the unmodified nucleotide by a modified version were applied 71 . Thus, in order to obtain a more detailed picture of the direct effect of single mRNA modifications on protein synthesis, a refined systematic approach was applied.…”
Section: Translational Regulation Mediated By Mrna Modificationsmentioning
confidence: 99%
“…Alternatively, mRNAs with a complete substitution of the unmodified nucleotide by a modified version were applied 71 . Thus, in order to obtain a more detailed picture of the direct effect of single mRNA modifications on protein synthesis, a refined systematic approach was applied.…”
Section: Translational Regulation Mediated By Mrna Modificationsmentioning
confidence: 99%
“…RNAs can be modified by means of chemical alterations to the ribose sugar (of particular importance is the 2′ position [45, 46]), the phosphate linkage and the individual bases (Fig. 1d) [4750]. RNAs delivered through nanoparticles, discussed later, are also typically modified in order to avoid recognition by endosomally expressed pattern recognition receptors [51].…”
Section: Delivery Materials and Chemical Modifications For Rnamentioning
confidence: 99%
“…They include N 6 -methyladenosine (m 6 A), N 1 -methyladenosine (m 1 A), 2-thiouridine (s2U), 5-methyluridine (m5U), 5-methoxyuridine (mo5U), N 1 -methylpseudouridine (m 1 ψ), 5-methylcytidine (m5C), 5-hydroxymethylcytidine (hm5C), 5-methoxycytidine (mo5C), and 2-methylguanosine (m2G) [9, 74]. A recent study identified m 1 ψ, mo5U, and ψ as the top three favorable nucleosides for mRNA modification, which significantly augmented protein expression [75]. In addition, combining ψ and m5C in modified mRNA can produce higher protein expression compared to a single modification [76, 77].…”
Section: Chemical Modification Of Mrnamentioning
confidence: 99%